Teenage girls : exploring issues adolescent girls face and strategies to help them - Olson, Ginny (Grand Rapids, Mich. : Zondervan ; El Cajon, CA : Youth Specialties, 2006)
Publisher description: Girls are more than just sugar and spice. We've all figured that out. What we haven't figured out completely is how they're wired, why they do the things they do, how the world around them affects their choices and opinions, and what that means for youth ministry--until now. In Teenage Girls, you'll find advice from counselors and veteran youth workers, along with helpful suggestions on how to minister to teenage girls. Each chapter includes discussion questions to help you and other youth workers process the issues your own students face and learn how you can help them and mentor them through this tumultuous time. In addition to the traditional issues people commonly associate with girls, such as eating disorders, self-image issues, and depression, author Ginny Olson will guide you through some of the new issues on the rise in girls' lives. You'll understand more about issues related to: Family; Addiction; Emotional well-being; Mental health; Physical welfare; Sexuality; Spirituality; Relationships.
1. Identity matters -- 2. An adolescent girl's body : in search of "normal" -- 3. An adolescent girl's body : body issues -- 4. An altered state : adolescent girls and self-injury -- 5. Dating matters -- 6. Sex matters -- 7. Emotional matters -- 8. Brain matters : cognitive and educational issues -- 9. Family Matters -- 10. Friendship matters -- 11. Faith matters.
Includes bibliographical references (p. 212-237).
Keywords: Church work with teenagers; Teenage girls -- Religious life